The Moderatism and Religious Conservatism Problems in the Middle of Covid-19 Pandemic Era - Abd Hannan; Fithriyah Rahmawati; Ahmad Imam Khairi (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2020)
This study discusses the phenomenon of religious conservatism and strengthening of religious moderation in the midst of the global pandemic, Covid-19. There are three problems of the research focuses in this study, namely religious moderation, religious conservatism, and the Covid-19 itself. By using a qualitative research and analysis based on social theory, this study has two important findings. Firstly, one of the problems that has often hampered the agenda for dealing with Covid-19 in many countries in the world, including in Indonesia that comes from conservatism in the religious sector. Contrasting the handling of Covid-19 with religious texts so as to make the response to Covid-19 not optimal and ineffective. In addition, the idea of religious moderatism in the midst of the Covid-19 pandemic requires three (3) things, they are the rationality, inclusivity, and contextually. Moderate in the rational sense means responding to Covid-19 with common sense and a logical attitude. It does not clash religion and science (medical), but puts them both in a dialogical and integrative manner. Meanwhile, being moderate in the sense of inclusion requires willingness and self-awareness to always take an active role. Comply with all forms of Covid-19 mitigation that have been mutually agreed upon based on consensus government policies. Moderatism in a contextual sense means that understanding Covid-19 requires comprehensive observation and attitude by considering its sociological aspects such as cultural dimensions, social systems and patterns of community interaction.